The Mangerial Grid / Key Orientations for Achieving Production Through People - Blake R. Robert; Mouton Srygley Jane (Gulf Publishing Company, 1964)
Preface, Introduction, Self Assessment of Key Managerial Orientations, Managerial Styles: Self Assessment of Managerial Styles, The Managerial Dilemma, The 9,1 Managerial Style, The 1,9 Managerial Style, The 1,1 Managerial Style, The 5,5 Managerial Style, The 9,9 Managerial style, Managerial Facades, Mixed Grid Theories, Career Accomplishment and Managerial Style, Analyzing Personal Managerial Styles, A 9,9 Approach to Organization Development, Organization Development and Performance, Trends and Practices of Management, Author and Subject Index.
Preface, Introduction, Self Assessment of Key Managerial Orientations, Managerial Styles: Self Assessment of Managerial Styles, The Managerial Dilemma, The 9,1 Managerial Style, The 1,9 Managerial Style, The 1,1 Managerial Style, The 5,5 Managerial Style, The 9,9 Managerial style, Managerial Facades, Mixed Grid Theories, Career Accomplishment and Managerial Style, Analyzing Personal Managerial Styles, A 9,9 Approach to Organization Development, Organization Development and Performance, Trends and Practices of Management, Author and Subject Index.